Implementing models of financial derivatives object oriented applications with VBA - Webber, Nick.; ebrary, Inc. (Chichester, U.K. : Wiley, 2011)
"A practical, step-by-step introduction to the design of pricing engines with VBA This book teaches students and practitioners the numerics and design of a powerful pricing tool in VBA. It leads the reader through the basics of VBA, from simple procedural code to the advanced design of systems and object-style applications. It also covers Monte Carlo and lattice methods and their implementation in VBA. Full implementation methods and code are provided for all methods discussed, making this an invaluable guide for portfolio managers, risk managers, and fund managers. Nick Webber (Warwick, UK) is a lecturer in finance at Warwick Business School. He specializes in interest rate modeling and computational finance"--
"This book teaches students and non-quant practitioners numerics and the design of a powerful pricing tool in VBA"--
pt. 1. A procedural Monte Carlo method in VBA -- pt. 2. Objects and polymorphism -- pt. 3. Using files with VBA -- pt. 4. Polymorphic factories in VBA -- pt. 5. Performance issues in VBA -- pt. 6. Variance reduction in the Monte Carlo method -- pt. 7. The Monte Carlo method : convergence and bias -- pt. 8. Valuing American options by simulation.
Includes bibliographical references and indexes.
Electronic reproduction.
Keywords: Microsoft Visual Basic for applications; Derivative securities -- Mathematical models; Electronic books